Amplification of useful vibration using on-off damping - Viet, La Duc (Vietnam Journal of Mechanics, 2020)
This paper points out how much useful vibration can be extracted from a base-excited oscillator, which is controlled by the on-off electrical damping. We study the class of on-off electrical damping controller, which switches the damping level from high to low and back at fixed times every quarter of period. The problem reduces to the maximization of a single-variable function. This result can open the new direction to amplify the useful vibration using controllable dampings.